Clinical outcome with low-dose valacyclovir in high-risk renal transplant recipients: a 10-year experience - Sund, Fredrik; Tufveson, Gunnar; Döhler, Bernd; Opelz, Gerhard; Eriksson, Britt-Marie (Nephrology, dialysis, transplantation, 2013)
Cytomegalovirus (CMV) remains an important pathogen in transplant patients, and valacyclovir (VACV) prophylaxis 8 g/day has been used in high-risk CMV-seromismatched [D+/R−] renal transplant patients to decrease CMV disease. Neurotoxic adverse effects have limited its use, and the aim of the present study was to retrospectively evaluate low-dose VACV prophylaxis, 3 g/day for 90 days after transplantation, in 102 D+/R− renal transplant patients.We compared patient and graft survival rates up to 5 years after transplantation with the data from the Collaborative Transplant Study Group (CTS) database. The incidence of CMV disease, rejection and neurotoxic adverse effects was analyzed up to 1 year after transplantation.The patient and graft survival rates up to 5 years were comparable with those derived from the CTS. CMV disease was diagnosed in 25% of the patients and 2% developed tissue-invasive CMV disease. The rejection frequency was 22% and neurotoxic adverse effects were seen in 2% of the patients.Low-dose VACV prophylaxis (3 g/day) for 90 days post-transplantation results in high patient and graft survival rates and reduces the incidence of CMV disease. Neurotoxic adverse effects are minimal. We believe that low-dose VACV prophylaxis should be considered to form one of the arms in future prospective comparison studies for the prevention of CMV disease in the high-risk D+/R− population of renal transplant patients.
Advance access publication 14 December 2012
Gesehen am 27.01.2022